The impact of exercise on prostate-specific antigen and testosterone in prostate cancer: a systematic review and meta-analysis - Fuxun Zhang; Zhirong Luo; Qi Xue; Xuyan Guo; Wei Zhang; Yang Xiong; Yong Jiao; Uzoamaka Adaobi Okoli; Geng Zhang (The Aging Male)
Background Exercise prescription can promote the rehabilitation of patients with prostate cancer (PCa). However, the effect of exercise intervention onserum levels of prostate-specific antigen (PSA) and testosterone remains unclear.Methods The primary outcome was the effect of exercise prescription on PSA level. The secondary outcome was the effect of exercise training on testosterone level. The pooled standardized mean difference (SMD) with 95% confidence interval (CI) was selected as the indicator. Meta-regression was conducted to assess the relationship between covariates and outcomes. Publication bias was evaluated using funnel plots and Egger’s test.Results The data of 594 patients from 8 randomized controlled trials (RCTs) were included and analyzed. Pooled effect of exercise intervention on PSA was 0.13 (95% CI: −0.04 to 0.29, I2 = 0.0%, p = 0.984), while the pooled effect on testosterone was 0.19 (95% CI: −0.00 to 0.39, I2 = 0.0%, p = 0.435). The meta-regression showed there was no significant association of age, body mass index, and the exercise duration with PSA or testosterone. No significant publication bias was detected in meta-analysis.Conclusions Although many benefits were documented, exercise intervention have no significant effect on PSA and testosterone levels in PCa patients.